Potential application of silver nanoparticles to control the infectivity of Rift Valley fever virus in vitro and in vivo; Nanomedicine: Nanotechnology, Biology and Medicine; Vol. 12, iss. 5 - Borrego B. Belen; Lorenzo G. I. Gema; Mota-Morales J. D. Josue; Almanza H. R. Horacio Reyez; Mateos F. A. Francisco; Lopez-Gil E. I. Elena; de la Losa N. A. Nuria; Burmistrov V. A. Vasily; Pestryakov A. N. Aleksey Nikolaevich; Brun A. Alejandro; Bogdanchikova Nina Nina (2016, 2016)
Title screen